Analisis Efektifitas Qanun Nomor 11 Tahun 2018 Tentang Perbankan Di Aceh - Tudini, Maiyuna; Musanna, Khadijatul; Fitri, Aulia (Sekolah Tinggi Agama Islam Al-Hikmah 2, 2025)
This study was conducted to examine the extent to which Qanun No. 11 of 2018 on Sharia Financial Institutions in Aceh has been implemented. Under this qanun, all financial institutions operating in Aceh are required to fully implement a sharia-based financial system. This study was conducted using a qualitative method with a literature review approach. This was done by reading and comparing various existing written sources, such as government reports, other people's research results, local media reports, and scientific papers. From the results obtained, this qanun has indeed succeeded in changing the form of financial institutions from the conventional system to the sharia system, and this happened in a relatively short period of time. However, in practice, there are still obstacles to its implementation. Many residents still do not fully understand Islamic banking. There are even small business owners who have never received proper guidance or direction on Islamic financing. On the other hand, not all Islamic financial institutions are ready to adapt their products and services to the needs of the community in their respective areas. This study concludes that while this regulation represents a significant step toward developing an Islamic economy in Aceh, its success ultimately depends on collaboration among all parties. The government, financial institutions, and the community must support one another. To improve the implementation of this regulation in the future, ongoing evaluations, regular public awareness campaigns, and improvements to supporting infrastructure and regulations are necessary. In this way, the benefits of this regulation can truly be felt by all residents of Aceh